Peran Pendekatan Sosial pada Pendidikan Islam Sebagai Solusi dalam Menghadapi Tantangan Perubahan Zaman - Muhammad Farhan Ferdino; Zuhdiyah; Tutut Handayani (Attractive : Innovative Education Journal, 2024)
This study aims to discuss the concept of the approach itself, its implementation, and its contributions from the social sciences, starting with an initial explanation of the concept through a social approach, its goals, and benefits in Islamic Education. The purpose of this research is to obtain library data related to the implementation of the social approach in Islamic religious education in facing the challenges of changing times. The issues are addressed using qualitative research, with data collection methods including library research. Data is obtained from the relevant books, paper and journals on social approach. The data is then analyzed using descriptive analysis techniques. The results of this research show that the social approach in Islamic education can be defined as a learning process that focuses on social interactions and relationships among people, while considering the values and teachings of Islam, it aims to provide guidance to society and learners in the social aspect regarding equality among all of Allah SWT's creations, and the role of social approach in Islamic education to face the changes of the times will continuously strive to shape learners who not only understand Islam deeply but also possess a high social awareness, are capable of actively participating in society, and are responsive to the changes and challenges they encounter